A STUDY ON RESPONSIBILITY ACCOUNTS ON STAKEHOLDERS - M.B Saikrishna; Kichu kurian (Research Parks Publishers, 2020)
This article investigates major points of the study on responsibility accounts on stakeholders. Therefore, research has been conducted on different accounts of stakeholders. Finally, outcomes and shortcomings of the research has been pointed as a result of the investigation